Synergistic effects of seaweed extract presoaking and foliar spray on the performance of paddy improved kavuni (CO 57) - Elamparithi , R; Sujatha, K; Alex Albert, V; Sivakumar, T; Gurusamy, A; Mini, M L (Plant Science Today, 2025)
Rice (Oryza sativa L.) is a staple food crop and a primary source of sustenance for more than half of the world's population. Seed treatments and foliar applications have emerged as effective methods to enhance growth and yield attributes. In this study, improved kavuni (CO 57) seeds were used for a field experiment conducted during the Samba season (2023). The experiment was designed using a Factorial Randomized Block Design with 15 treatments and three replications, focusing on foliar spray applications. The primary objective was to evaluate the impact of Sargassum myricocystum, Kappaphycus alvarezii methanol extract and foliar spray on rice growth and productivity. The results revealed that the combined application of presoaking seeds in 0.5 % Sargassum myricocystum methanol extract with a foliar spray of 2.5 % seaweed extract at the panicle initiation and flowering stages (T1F2) significantly enhanced plant growth and yield parameters. Higher plant height (121 cm), leaf area index (4.85), dry matter production (5180 kg ha- ¹), productive tillers (281 m- ²), filled seeds per panicle (170), 1000 seed weight (22.34 g), seed yield (4552 kg ha- ¹) and straw yield (6370 kg ha- ¹) were recorded under T1F2 compared to other treatments. The use of organic input seaweed extracts, improved plant quality and yield sustainably without harming the natural ecosystem. This study highlights the significant potential of seaweed extracts in enhancing overall crop performance, leading to optimal plant growth characteristics and yield attributes. The findings emphasise the role of organic inputs in promoting sustainable agriculture, contributing to environmental conservation while supporting food security.